Low RASSF6 expression in pancreatic ductal adenocarcinoma is associated with poor survival - Ye, Hui-Lin (World J Gastroenterol, 2015)
AIM: To analyze RASSF6 expression in pancreatic ductal adenocarcinoma (PDAC) and to determine whether RASSF6 has an independent prognostic value in PDAC. METHODS: We studied RASSF6 expression in 96 histologically confirmed PDAC samples and 20 chronic pancreatitis specimens using immunohistochemistry and real-time quantitative reverse transcription-PCR. PDAC issues were then classified as RASSF6 strongly positive, weakly positive or negative. RASSF6 mRNA and protein expression in PDAC samples with strong positive staining was further evaluated using real-time PCR and Western blot analysis. Lastly, correlations between RASSF6 staining and patients’ clinicopathological variables and outcomes were assessed. RESULTS: RASSF6 was negatively expressed in 51 (53.1%) PDAC samples, weakly positively expressed in 29 (30.2%) and strongly positively expressed in 16 (16.7%), while its expression was much higher in para-tumor tissues and chronic pancreatitis tissues. Positive relationships between RASSF6 expression and T-stage (P = 0.047) and perineural invasion (P = 0.026) were observed. The median survival time of strongly and weakly positive and negative RASSF6 staining groups was 33 mo, 15 mo and 11 mo, respectively. Cox multivariate analysis indicated that RASSF6 was an independent prognostic indicator of overall survival in patients with PDAC. A survival curve analysis revealed that increased RASSF6 expression was correlated with better overall survival (P = 0.009). CONCLUSION: RASSF6 expression is an independent biomarker of an unfavorable prognosis in patients with PDAC.